The tendency of factors influencing the state of psychological readiness of an individual for professional activity - Khikmatovich, Kurbanov Ikhtiyor (Journal of Multidisciplinary Academic and Practice Studies, 2025)
Purpose: This study aims to analyze the theoretical model of psychological readiness for professional activity and identify effective methods for its formation among university students, particularly those studying psychology. The research emphasizes the integration of cognitive, emotional, and motivational components to prepare students for future professional roles. Research Methodology: A mixed-method approach was used, combining theoretical modeling and empirical analysis. Diagnostic tools were applied to assess students’ psychological readiness, while experimental training sessions were implemented to test the proposed formation method. The model was evaluated through structured observation, self-assessment questionnaires, and competence-based analysis. Results: Findings demonstrate that the formation of psychological readiness is significantly influenced by self-process activation, reflective thinking, and competence integration. The developed method enhanced students’ self-awareness, professional motivation, and ability to apply theoretical knowledge in practical contexts. The study confirmed that readiness for professional activity can be intentionally cultivated through targeted educational interventions. Conclusions: The research validates that psychological readiness is a dynamic construct comprising self-regulation, motivation, and practical competence. The competence-based and self-activation approaches provide an effective framework for professional preparation. Limitations: The study was limited to psychology students within a single university context, and longitudinal effects were not examined. Broader application across disciplines requires further study. Contribution: This study contributes to educational psychology by presenting an empirically tested model and a method for developing psychological readiness aligned with modern competence-based education principles.